Thyroid abnormality in abnormal uterine bleeding: an observational study from Medical College in Western UP, India - Singh, Prachi; Dubey, Prashant; Yadav, Shweta; Yadav, Sachin Singh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abnormal Uterine Bleeding (AUB) is one of the commonest gynecological complain in reproductive age group. Menstrual abnormalities are commonly seen when there is any alteration in thyroid function. Objective of present study was to investigate the prevalence of AUB and to determine the menstrual pattern in cases with thyroid dysfunction. Methods: The present cross sectional observational study was conducted Teerthankar Mahaveer Medical College and Research Center Moradabad. Total 400 cases presenting with AUB were included in the study. Routine blood test, ultrasonography and thyroid function tests were done in these cases. Results: Among all the cases presenting with menstrual abnormalities 26% had hypothyroidism and 9% have hyperthyroidism and rest had euthyroid status. Menorrhagia (45.2%) and polymenorrhoea (37.5%) were commonest menstrual abnormality seen in cases with hypothyroidism. Most cases with hyperthyroidism presented with hypomenorrhoea (27.8%). Conclusions: Thyroid function abnormality is common in cases presenting with AUB and it gets relieved in correcting hormonal imbalance.